Ovicidal toxicity of plant essential oils and their major constituents against two mosquito vectors and their non-target aquatic predators - Tanapoom Moungthipmalai; Cheepchanok Puwanard; Jirapon Aungtikun; Sirawut Sittichok; Mayura Soonwera (My University, 2022)
Abstract Plant essential oil (EO) is a natural alternative to synthetic chemical insecticides for mosquito control. EOs from Citrus aurantium L., Cymbopogon citratus (Stapf.), and Cinnamomum verum (J. Presl.) were selected for topical assay of their ovicidal activity against Aedes aegypti L. and Aedes albopictus (Skuse). Their efficacy was compared to that of 1% ( w/w ) temephos. In addition, their non-toxicity against aquatic mosquito predators, Poecilia latipinna and Poecilia reticulate , was tested. Found by GC-MS analysis, the major constituent of C . verum EO was trans - cinnamaldehyde, of C . aurantium EO was d-limonene, and of C . citratus EO was geranial. Both C . verum EO and trans -cinnamaldehyde at a high concentration (30,000 ppm) exhibited high ovicidal activity against Ae . aegypti and Ae . albopictus eggs after 48 h of incubation with an inhibition rate of 91.0–93.0% for C . verum EO and 96.7–95.2% for trans -cinnamaldehyde. The combination of C . verum EO + geranial exhibited the strongest synergistic inhibition activity (100%) against the two mosquito vectors and was five times more effective than temephos. Moreover, they were not toxic to the non-target fishes. As a safe ovicidal agent for mosquito egg control, the combination of C . verum EO + geranial has excellent potential.
Keywords: Aedes albopictus; Insect Pest Control Strategies